Investigasi Pengaruh Partisipasi dan Hasil Belajar Matematika terhadap Resiliensi Siswa Sekolah Dasar: Studi Kuantitatif Eksplanatori - Maulyda, Mohammad Archi; Hidayati, Vivi Rachmatul; Fauzi, Asri (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to analyze the influence of student participation and mathematics achievement on students' mathematical resilience at the elementary school level. The research design employs a quantitative approach with an explanatory design to examine the causal relationships between the independent variables (participation and achievement) and the dependent variable (resilience). The participants in this study were 158 elementary school students from Mataram City, selected using convenience sampling. Data were collected through questionnaires to measure student participation, report card grades for mathematics achievement, and a resilience questionnaire tailored for elementary school students. Data analysis was performed using normality tests, non-parametric regression, and RT-ANCOVA. The results indicate that student participation significantly influences mathematical resilience, while mathematics achievement does not have a significant effect. Gender and geographic factors also affect mathematical resilience, with female students and those from urban areas exhibiting higher resilience compared to male students and those from mountainous or coastal areas. This study highlights the importance of active student involvement in mathematics learning and the need to address gender and geographic disparities in mathematics education. The findings offer insights into educational policies to support the development of students' resilience in mathematics.